Electrochemical (Bio)Sensors Enabled by Fused Deposition Modeling-Based 3D Printing: A Guide to Selecting Designs, Printing Parameters, and Post-Treatment Protocols - Stefano, Jéssica Santos; Kalinke, Cristiane; da Rocha, Raquel Gomes; Rocha, Diego Pessoa; da Silva, Vinicius Aparecido Oliani Pedro; Bonacin, Juliano Alves; Angnes, Lúcio; Richter, Eduardo Mathias; Janegitz, Bruno Campos; Muñoz, Rodrigo Alejandro Abarza (Analytical chemistry (Washington), 2022)
The 3D printing (or additive manufacturing, AM) technology is capable to provide a quick and easy production of objects with freedom of design, reducing waste generation. Among the AM techniques, fused deposition modeling (FDM) has been highlighted due to its affordability, scalability, and possibility of processing an extensive range of materials (thermoplastics, composites, biobased materials, etc.). The possibility of obtaining electrochemical cells, arrays, pieces, and more recently, electrodes, exactly according to the demand, in varied shapes and sizes, and employing the desired materials has made from 3D printing technology an indispensable tool in electroanalysis. In this regard, the obtention of an FDM 3D printer has great advantages for electroanalytical laboratories, and its use is relatively simple. Some care has to be taken to aid the user to take advantage of the great potential of this technology, avoiding problems such as solution leakages, very common in 3D printed cells, providing well-sealed objects, with high quality. In this sense, herein, we present a complete protocol regarding the use of FDM 3D printers for the fabrication of complete electrochemical systems, including (bio)sensors, and how to improve the quality of the obtained systems. A guide from the initial printing stages, regarding the design and structure obtention, to the final application, including the improvement of obtained 3D printed electrodes for different purposes, is provided here. Thus, this protocol can provide great perspectives and alternatives for 3D printing in electroanalysis and aid the user to understand and solve several problems with the use of this technology in this field.